Deep foundations and geotechnical in situ testing : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Liang, Robert Y.; Zhang, Feng, 1959-; Yang, Ke, 1978- (Geotechnical special publication ;, 2010)
This Geotechnical Special Publication, Deep Foundations and Geotechnical in Situ Testing, contains 49 papers examining the areas of deep foundations and in situ geotechnical testing and monitoring techniques. This proceedings offers the latest and most current thinking on topics such as piled raft system and soil-structure interaction; deep foundations; innovative foundations; and in situ testing.